2010
DOI: 10.1111/j.1365-2613.2009.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased calcium influx in the presence of ethanol in mouse pancreatic acinar cells

Abstract: The effects of alcohol on Ca(2+) signalling remains poorly understood. Here we have investigated the effects of acute ethanol exposure on Ca(2+) influx in mouse pancreatic acinar cells. Cells were loaded with fura-2 and the changes in fluorescence were monitored by spectrofluorimetry and imaging analysis. Stimulation of cells with 20 pM cholecystokinin evoked an oscillatory pattern in [Ca(2+)](c), both in the presence and in the absence of extracellular Ca(2+). Stimulation of cells with cholecystokinin in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…Del Castillo-Vaquero et al . [9] showed that acute application of ethanol at clinically relevant concentrations (1–50 mmol/l) to isolated acinar cells resulted in Ca 2+ influx due to the production of oxidative metabolites of alcohol. Together, the studies implicate a role for alcohol metabolites in acinar cell injury through aberrant Ca 2+ signals.…”
Section: Ethanol Metabolites and Ca2+mentioning
confidence: 99%
“…Del Castillo-Vaquero et al . [9] showed that acute application of ethanol at clinically relevant concentrations (1–50 mmol/l) to isolated acinar cells resulted in Ca 2+ influx due to the production of oxidative metabolites of alcohol. Together, the studies implicate a role for alcohol metabolites in acinar cell injury through aberrant Ca 2+ signals.…”
Section: Ethanol Metabolites and Ca2+mentioning
confidence: 99%
“…Although alcohol abuse has been long recognized as a risk factor for acute and chronic pancreatitis, the molecular mechanism mediating the sensitizing affect of EtOH on secretagogue signaling in acinar cells has remained largely unresolved (26,27). In this study we show that RKIP is a substrate for EtOHinduced PKC-dependent phosphorylation and a critical mediator of EtOH-induced sensitization of secretagogue signaling.…”
Section: Discussionmentioning
confidence: 62%
“…Exposing either experimental animals or isolated pancreatic acinar cells to EtOH sensitizes the cells to physiologic secretagogue stimulation (22)(23)(24)(25)(26) and deregulates normal agonist-in-duced Ca 2ϩ responses and zymogen activation (27,28). Specifically, it has been shown that after treatment of isolated pancreatic acinar cells either with EtOH or its non-oxidative metabolites, physiological concentrations of secretagogue induces sustained increases in [Ca 2ϩ ] cyto that are no longer limited to the apical pole but spread throughout the acinar cell (28,29).…”
mentioning
confidence: 99%
“…A recent study by Castillo‐Vaquero et al 61 . suggests an additional source for raised intracellular calcium in alcohol‐exposed acinar cells.…”
Section: Effect Of Alcohol On Pancreatic Enzymesmentioning
confidence: 95%